Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To evaluate the integral
[tex]\[ \int \frac{\cos x}{6 \sin ^2 x + 7 \sin x} \, dx, \][/tex]
we follow these steps:
1. Substitution:
Let [tex]\( u = \sin x \)[/tex]. Then, [tex]\( du = \cos x \, dx \)[/tex]. This simplifies our integral in terms of [tex]\( u \)[/tex]:
[tex]\[ \int \frac{\cos x}{6 \sin^2 x + 7 \sin x} \, dx = \int \frac{1}{6u^2 + 7u} \, du. \][/tex]
2. Partial Fraction Decomposition:
We decompose the integrand [tex]\( \frac{1}{6u^2 + 7u} \)[/tex]:
[tex]\[ \frac{1}{6u^2 + 7u} = \frac{1}{u(6u + 7)}. \][/tex]
This can be written using partial fractions:
[tex]\[ \frac{1}{u(6u + 7)} = \frac{A}{u} + \frac{B}{6u + 7}, \][/tex]
where [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are constants to be determined. To find [tex]\( A \)[/tex] and [tex]\( B \)[/tex], we solve the equation:
[tex]\[ 1 = A(6u + 7) + Bu. \][/tex]
Setting [tex]\( u = 0 \)[/tex], we find:
[tex]\[ 1 = 7A \implies A = \frac{1}{7}. \][/tex]
To find [tex]\( B \)[/tex], set [tex]\( u = -\frac{7}{6} \)[/tex]:
[tex]\[ 1 = \frac{1}{7}(-\frac{7}{6} \cdot 6 + 7) + B(-\frac{7}{6}) \implies 1 = \frac{1}{7} \cdot 0 - \frac{7}{6}B \implies B = -\frac{6}{7}. \][/tex]
Therefore, the partial fractions decomposition is:
[tex]\[ \frac{1}{u(6u + 7)} = \frac{1}{7u} - \frac{6}{7(6u + 7)}. \][/tex]
3. Integration:
Now, we integrate each term separately:
[tex]\[ \int \left( \frac{1}{7u} - \frac{6}{7(6u + 7)} \right) \, du = \frac{1}{7} \int \frac{1}{u} \, du - \frac{6}{7} \int \frac{1}{6u + 7} \, du. \][/tex]
These integrals are straightforward:
[tex]\[ \int \frac{1}{u} \, du = \ln|u|, \][/tex]
and for the second integral, we use substitution [tex]\( v = 6u + 7 \)[/tex], then [tex]\( dv = 6 \, du \)[/tex], so [tex]\( du = \frac{dv}{6} \)[/tex]:
[tex]\[ \int \frac{1}{6u + 7} \, du = \frac{1}{6} \int \frac{1}{v} \, dv = \frac{1}{6} \ln|v| = \frac{1}{6} \ln|6u + 7|. \][/tex]
Putting it all together:
[tex]\[ \frac{1}{7} \int \frac{1}{u} \, du - \frac{6}{7} \int \frac{1}{6u + 7} \, du = \frac{1}{7} \ln|u| - \frac{6}{7} \cdot \frac{1}{6} \ln|6u + 7| = \frac{1}{7} \ln|u| - \frac{1}{7} \ln|6u + 7|. \][/tex]
4. Back Substitute:
Finally, revert back from [tex]\( u = \sin x \)[/tex]:
[tex]\[ \frac{1}{7} \ln|\sin x| - \frac{1}{7} \ln|6\sin x + 7|. \][/tex]
Combine the logarithms:
[tex]\[ \frac{1}{7} \left( \ln|\sin x| - \ln|6 \sin x + 7| \right) = \frac{1}{7} \ln \left| \frac{\sin x}{6 \sin x + 7} \right|. \][/tex]
So, the evaluated integral is:
[tex]\[ \int \frac{\cos x}{6 \sin^2 x + 7 \sin x} \, dx = -\frac{\ln(6 \sin x + 7)}{7} + \frac{\ln(\sin x)}{7} + C, \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
[tex]\[ \int \frac{\cos x}{6 \sin ^2 x + 7 \sin x} \, dx, \][/tex]
we follow these steps:
1. Substitution:
Let [tex]\( u = \sin x \)[/tex]. Then, [tex]\( du = \cos x \, dx \)[/tex]. This simplifies our integral in terms of [tex]\( u \)[/tex]:
[tex]\[ \int \frac{\cos x}{6 \sin^2 x + 7 \sin x} \, dx = \int \frac{1}{6u^2 + 7u} \, du. \][/tex]
2. Partial Fraction Decomposition:
We decompose the integrand [tex]\( \frac{1}{6u^2 + 7u} \)[/tex]:
[tex]\[ \frac{1}{6u^2 + 7u} = \frac{1}{u(6u + 7)}. \][/tex]
This can be written using partial fractions:
[tex]\[ \frac{1}{u(6u + 7)} = \frac{A}{u} + \frac{B}{6u + 7}, \][/tex]
where [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are constants to be determined. To find [tex]\( A \)[/tex] and [tex]\( B \)[/tex], we solve the equation:
[tex]\[ 1 = A(6u + 7) + Bu. \][/tex]
Setting [tex]\( u = 0 \)[/tex], we find:
[tex]\[ 1 = 7A \implies A = \frac{1}{7}. \][/tex]
To find [tex]\( B \)[/tex], set [tex]\( u = -\frac{7}{6} \)[/tex]:
[tex]\[ 1 = \frac{1}{7}(-\frac{7}{6} \cdot 6 + 7) + B(-\frac{7}{6}) \implies 1 = \frac{1}{7} \cdot 0 - \frac{7}{6}B \implies B = -\frac{6}{7}. \][/tex]
Therefore, the partial fractions decomposition is:
[tex]\[ \frac{1}{u(6u + 7)} = \frac{1}{7u} - \frac{6}{7(6u + 7)}. \][/tex]
3. Integration:
Now, we integrate each term separately:
[tex]\[ \int \left( \frac{1}{7u} - \frac{6}{7(6u + 7)} \right) \, du = \frac{1}{7} \int \frac{1}{u} \, du - \frac{6}{7} \int \frac{1}{6u + 7} \, du. \][/tex]
These integrals are straightforward:
[tex]\[ \int \frac{1}{u} \, du = \ln|u|, \][/tex]
and for the second integral, we use substitution [tex]\( v = 6u + 7 \)[/tex], then [tex]\( dv = 6 \, du \)[/tex], so [tex]\( du = \frac{dv}{6} \)[/tex]:
[tex]\[ \int \frac{1}{6u + 7} \, du = \frac{1}{6} \int \frac{1}{v} \, dv = \frac{1}{6} \ln|v| = \frac{1}{6} \ln|6u + 7|. \][/tex]
Putting it all together:
[tex]\[ \frac{1}{7} \int \frac{1}{u} \, du - \frac{6}{7} \int \frac{1}{6u + 7} \, du = \frac{1}{7} \ln|u| - \frac{6}{7} \cdot \frac{1}{6} \ln|6u + 7| = \frac{1}{7} \ln|u| - \frac{1}{7} \ln|6u + 7|. \][/tex]
4. Back Substitute:
Finally, revert back from [tex]\( u = \sin x \)[/tex]:
[tex]\[ \frac{1}{7} \ln|\sin x| - \frac{1}{7} \ln|6\sin x + 7|. \][/tex]
Combine the logarithms:
[tex]\[ \frac{1}{7} \left( \ln|\sin x| - \ln|6 \sin x + 7| \right) = \frac{1}{7} \ln \left| \frac{\sin x}{6 \sin x + 7} \right|. \][/tex]
So, the evaluated integral is:
[tex]\[ \int \frac{\cos x}{6 \sin^2 x + 7 \sin x} \, dx = -\frac{\ln(6 \sin x + 7)}{7} + \frac{\ln(\sin x)}{7} + C, \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.